Effect of lidocaine pumped through hepatic artery to relieve pain of hepatic artery infusion chemotherapy - Zhang, Renjie; Liao, Yiling; Yang, Xiaoya; Tian, Hengyu; Wu, Shenfeng; Zeng, Qingteng; He, Qinghua; Zhang, Ruikun; Wei, Chunshan; Liu, Jialin (Frontiers in Surgery, 2024)
Background This study aims to explore the analgesic effect of lidocaine pumped administered through the hepatic artery used induring hepatic artery infusion chemotherapy (HAIC) for hepatocellular carcinoma (HCC). Methods A total of 45 HCC patients were randomly divided into a study group and a control group. Both groups were injected withreceived oxaliplatin (OXA) based FOLFOX protocol by via electronic infusion pump. The study group was continuously infused with 100 mg of lidocaine during HAIC, while 5% glucose solution was infused in the same way as described above. The cChanges of in vital signs, visual analogue score (VAS) and general comfort score (GCQ scale) were recorded before surgery (Time point 0), at the end of infusion (Time point 01), 1 hour after HAIC (Time point 02), 3 hours after HAIC (Time point 03) and 6 hours after HAIC (Time point 04). Results At each point of time from Time point 0 through Time point 04, the differences in MAP, RR and SPO2 between the two groups were not statistically significant (P＞0.05). At each point of time from Time point 01 through Time point 04, the mean VAS scores in the study group were smaller and GCQ scores were higher than those in the control group, and the differences were both statistically significant (P < 0.05). Conclusions Lidocaine infusion through the hepatic artery during HAIC effectively reduces intraoperative and postoperative pain and improves patient satisfaction with pain management, making it a valuable technique for clinical practice.